Music in the zarzuelas of Severino Reyes ("Lola Basyang") - Samson, Helen de la Fuente 1944- (Diliman, Quezon City The University of the Philippines Press, 2016)
"Severino Reyes (1861-1942), writer and dramatist, wrote the libretto to a total of twenty zarzuelas in which he worked closely with composers ranging from Fulgencio Tolentino (1870-1940) to Antonio Molina (1894-1980). Unfortunately, only eleven of these works have extant music today. Nevertheless, they present a good cross section of musical theory and practice in the Philippines early in the twentieth century"--Page 4 of cover.
Includes bibliographical references (pages 179-183) and index.
Keywords: Reyes, Severino -- 1861-1942 -- Criticism and interpretation; Tolentino, Fulgencio -- Criticism and interpretation; Molina, Antonio J. -- 1928- -- Criticism and interpretation; Music -- Philippines -- History and criticism; Zarzuelas -- Scores; Zarzuelas -- Librettos; Music appreciation -- Philippines